Pengaruh Perhatian Orang Tua terhadap Kedisiplinan Belajar Matematika - Fauzia Zukli; Haida Fitri; Tasnim Rahmat; M. Imamuddin (Journal on Education, 2023)
The purpose of this study was to determine the significant influence of parental attention on the discipline of learning mathematics. The hypothesis in this study is "There is a significant influence of parental attention on the discipline of learning mathematics. This type of research is correlation research. The population is 54 people and the sample used is the entire population of class VIII MTsN 7 Fifty Cities for the 2021/2022 academic year. The instrument used is the angle to determine the attention of parents and learning discipline. The statistical analysis technique used is Regression Analysis. The results of this study obtained a correlation value of rxy = 0.98 and a coefficient of determination of 95.06% from changing the hypothesis, for the significant influence of parental attention on the discipline of learning mathematics for class VIII MTsN 7 Fifty Kota obtained zcount = 3.37 and ztable=1.96 at 0.05 confidence. If Fcount > Ftable, then the research hypothesis is accepted. This means that there is an influence indicating parental attention to the discipline of learning mathematics in class VIII MTsN 7 Fifty Kota.